Immune-mediated hemolytic anemia in a dog: Case report (Research, Society and Development, 2024)
The objective of this article is to present a clinical case report of a dog with hemolytic anemia. Immune-mediated hemolytic anemia is a disease characterized by a decrease in the number of circulating erythrocytes, resulting from hemolysis, whether intra or extravascular. It is a relatively common condition in dogs and less frequently seen in cats. It may have a primary origin, that is, autoimmune, or be secondary to various causes, such as infections, neoplasms or even induced by medications and foods. The clinical signs most frequently observed in dogs with immune-mediated hemolytic anemia include weakness, apathy, loss of appetite, pale mucous membranes or jaundice, exercise intolerance, tachycardia, tachypnea, difficulty breathing, fever, vomiting, diarrhea and changes in urine color. Treatment aims to control the underlying disease and correct anemia, through blood transfusion, in addition to establishing immunosuppressive therapy with corticosteroids or other cytotoxic agents. Considering the importance of this pathology and the difficulty in diagnosing it, a general and updated approach was carried out, with the aim of providing more information to the veterinary clinician.